Social Relations of Former Drug Users after Rehabilitation in Bengkulu City - Syahputra, Dandy Fahturozy; Suminar, Panji; Widiyarti, Diyas (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2025)
This study examines how former drug users in Bengkulu City experience and reconstruct social relations after rehabilitation. Rehabilitation does not end with medical treatment but continues in everyday interaction where acceptance, trust, and stigma are negotiated. Using a qualitative approach guided by symbolic interactionism, this study draws on in depth interviews and observation involving former drug users, family members, and rehabilitation staff. The analysis focuses on how meanings are formed through interaction and how these meanings shape post rehabilitation identity and social participation. The findings show that post rehabilitation social relations are rebuilt gradually through repeated interaction in family, community, and workplace settings. Family support plays a central role by providing symbolic recognition that legitimizes identity change, although it is often accompanied by supervision and conditional trust. Community relations tend to be ambivalent. Participation in social and religious activities can facilitate inclusion, while stigma and social memory continue to limit full acceptance. Institutional post rehabilitation programs, including mentoring and skills training, strengthen reintegration by offering both practical resources and social legitimacy. At the same time, persistent stigma and limited access to employment remain significant constraints. This study concludes that social reintegration after rehabilitation is an ongoing social process shaped by interaction, meaning making, and agency. By situating recovery within the semi urban context of Bengkulu City, this study contributes to sociological discussions on stigma, identity reconstruction, and social relations, and highlights the importance of strengthening family involvement, reducing community-based stigma, and sustaining inclusive post rehabilitation support.